Encapsulation of NH2-MIL-101(Fe) with dialdehyde starch through Schiff-base imine: A development of a pH-responsive core-shell fluorescent nanocarrier for doxorubicin delivery - Ali Mohammadzadeh; Siamak Javanbakht; Reza Mohammadi (Carbohydrate Polymer Technologies and Applications)
This study focuses on developing a pH-sensitive drug delivery system by combining a porous metal-organic framework (MOF) with a natural polymer. To achieve this, a novel gatekeeping system was designed using biocompatible dialdehyde starch (DAS) and MOFs (NH2-MIL-101(Fe)) for cancer therapy. Fluorescent porous iron-based MOFs (NH2-MIL-101(Fe)), composed of 2-amino benzene dicarboxylic acid (NH2H2BDC) and iron (III) chloride hexahydrate (FeCl3.6H2O), were synthesized via a one-step hydrothermal method. Doxorubicin (DOX) was loaded into the MOF pores with a drug loading efficiency of 92 ± 0.5 %. To enable controlled drug release, the MOF surface was coated with biocompatible DAS through Schiff-base imine reactions, forming a core-shell structure with gatekeeping properties. These Schiff-base bonds ensured stability under physiological conditions but selectively degraded in mildly acidic environments, enabling pH-responsive release. In vitro studies showed that DOX release was pH-dependent, with a release rate of less than 8 ± 0.5 % at pH 7.4 compared to approximately 70 ± 0.5 % at pH 5 over 10 days. Cytotoxicity tests demonstrated significant effects of NH2-MIL-101(Fe)/DOX@DAS on HeLa cells (IC50: ∼100 µg/mL). Overall, NH2-MIL-101(Fe)/DOX@DAS exhibits strong potential as an effective and safe controlled-release nanocarrier for cancer treatment.